Predictors of School Success in Romania. Family Background, School Factors, and Community Factors - Tufiş, Paula Andreea (Calitatea Vieții, 2008)
The paper analyses the relationship between family background, school characteristics, community characteristics, and children’s school success in Romania, in 2001. The analysis is placed in the context of the debates regarding the relative importance of family background factors, school factors and neighborhood/ community factors in explaining the variation in children’s academic achievement. While research disentangling these relationships is abundant for developed countries and for several developing countries in Latin America, sub-Saharian Africa, and South and East Asia, the Central and Eastern European countries are underrepresented in this type of research. The empirical analysis on educational inequality in Romania undertaken here will also be placed in the context of the educational reforms that accompanied the fall of communism in 1989. The literature review will draw mainly on the contributions to the field based on the American context and some earlier contributions regarding the context of developing countries. It will also present the opinions of several scholars examining the context of educational reforms after the fall of communism in Central and Eastern Europe and in Romania, in particular. The present work will draw on these theoretical bases and the results of an empirical analysis on Romanian fourth graders in an attempt to sketch an image of several factors that contribute to inequalities among children in school success, in Romania.